Ketogenic diet as a therapeutic intervention for obsessive-compulsive disorder: a case series of three patients - MacDonald, Aaron John; Palmer, Christopher Michael (Frontiers in Nutrition, 2025)
IntroductionThe ketogenic diet is being explored as a therapeutic intervention for the treatment of neuropsychiatric disorders. Emerging research suggests that these conditions share common pathophysiologies, with the ketogenic diet showing promise in addressing these. This study reports three individuals who reduced their symptoms of obsessive-compulsive disorder (OCD) after adopting a ketogenic diet.MethodsParticipants were recruited through personal and professional networks among the authors. Each patient was interviewed, and evidence of their mental health history was collected. Their OCD symptoms were retrospectively assessed before and after adopting the diet using the Yale-Brown Obsessive Compulsive Scale (Y-BOCS).ResultsThe three participants in this case series have all achieved remission of their symptoms and are medication-free. The diet implementation reduced their average Y-BOCS scores by 21 points, corresponding to a mean decrease of 90.5%. In all cases, deviations from the ketogenic diet resulted in a return of their symptoms.ConclusionThe ketogenic diet may be an effective treatment for obsessive-compulsive disorder. Its capacity to improve the metabolic dysfunction associated with OCD may target the underlying mechanisms of the disorder. Controlled clinical trials of the ketogenic diet as a treatment for OCD are warranted.